If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + -3w)(3y + -6w + 7) = 0 Reorder the terms: (-3w + 4y)(3y + -6w + 7) = 0 Reorder the terms: (-3w + 4y)(7 + -6w + 3y) = 0 Multiply (-3w + 4y) * (7 + -6w + 3y) (-3w * (7 + -6w + 3y) + 4y * (7 + -6w + 3y)) = 0 ((7 * -3w + -6w * -3w + 3y * -3w) + 4y * (7 + -6w + 3y)) = 0 Reorder the terms: ((-21w + -9wy + 18w2) + 4y * (7 + -6w + 3y)) = 0 ((-21w + -9wy + 18w2) + 4y * (7 + -6w + 3y)) = 0 (-21w + -9wy + 18w2 + (7 * 4y + -6w * 4y + 3y * 4y)) = 0 Reorder the terms: (-21w + -9wy + 18w2 + (-24wy + 28y + 12y2)) = 0 (-21w + -9wy + 18w2 + (-24wy + 28y + 12y2)) = 0 Reorder the terms: (-21w + -9wy + -24wy + 18w2 + 28y + 12y2) = 0 Combine like terms: -9wy + -24wy = -33wy (-21w + -33wy + 18w2 + 28y + 12y2) = 0 Solving -21w + -33wy + 18w2 + 28y + 12y2 = 0 Solving for variable 'w'. The solution to this equation could not be determined.
| 10+2x=n | | 9+5x=104 | | (X+25)+3x=435 | | J-11/9=5 | | (a^3)+72=8 | | 14-3x=18-4x | | 9y+30+6+6y=13y-2y | | 7(x-2)-4(x+1)=-21 | | 6(2x-2)=45+5x | | 9y+3016+6y=13y-2y | | (v-2w-2)(v-4)=0 | | 2=200/w^2 | | 2x+8+x+1=0 | | 3(20x+50)=510 | | 5x+24(x-2)=184 | | -5x+40=6x-(70) | | 40x+7=40d+34 | | (27x^4)+3p=2p | | 2m+3=2m-3 | | 6r^3+2r^2-48r= | | 3y-7=80 | | H-3=12 | | (3v-w-2)(7v+6)=0 | | 4(x+2)+3(x-6)=-3 | | 5x-20=x-2.4 | | 5a/24÷1/12 | | 9x/-102/3 | | -5t=-35 | | ln[(x-9)/((x^(2)-81)^(5))]^((2)/(5)) | | (3x+21)=(6x+15) | | 7p+21+9=10p-10-3p | | X^4-5x^2=-6 |